Pemahaman Vaksin Covid-19 Pada Mahasiswa Lulusan Pertama Barunawati Semarang - Aryani, Lenci (Jurnal Abdimas Jatibara, 2022)
The Covid-19 vaccination provides immunity to society as a whole. This is very vulnerable in school children who have face-to-face activities in class, the immune level of students and teachers must be maximized. Objectives: this service is to provide a level of understanding of vaccination activities for school students. Methods: Carried out by giving a pre-test to junior high school students related to the covid-19 vaccination, followed by the delivery of material and after that a post-test is given to determine understanding related to the material provided. Results: The pre-test showed that the average knowledge of students was 12.67%. Then there was an increase in students' knowledge of vaccination by 14.13%. Conclusioins: there is an increase in students' knowledge of the use of vaccination in the school environment